232k views
4 votes
-What is the product of (a - 1) and (2a + 2)?A 2(a2 - 2)B 2(a2 - 1)C a2 + 4a - 2D2a2 - 4a - 2-

User Muhammedv
by
6.3k points

1 Answer

3 votes

The product of the sum and difference binomials is


(x-y)(x+y)=x^2-y^2

We will use this rule to solve the question

We need to find the product of (a - 1) and (2a + 2)

At first, we will take 2 as a common factor from the second bracket


\begin{gathered} 2a+2=2((2a)/(2)+(2)/(2)) \\ 2a+2=2(a+1) \end{gathered}

Now, we will multiply (a - 1) by 2(a + 1)


(a-1)(2a-2)=2(a-1)(a+1)

By using the rule of the product of the sum and difference above, then


\begin{gathered} 2(a-1)(a+1)=2(a^2-1^2) \\ 2(a-1)(a+1)=2(a^2-1) \end{gathered}

The answer is B

User Sleblanc
by
5.7k points